Users' satisfaction on parking facility in shopping complexes in Penang / Siti Zulaikha Wan Ibrahim - Siti Zulaikha, Wan Ibrahim (2018)
Parking provision and management is an important issue for both public authorities and private operators running those facilities. The parking problems drive the traffic professionals to seek for more efficient solutions as to how the parking system can be used more efficiently and how parking planning and management can be improved. The growth in population and cars circulating has brought the parking experience to the forefront of the overall shopping experience. Parking facilities is important for the success of a mall because most customers will look for a space to park their cars. The aim of this research is to analyse the user satisfaction on the efficiency of parking facilities in shopping complexes. The purpose of this study is to determine the parking facility available at the shopping complexes, identify the users’ level of satisfaction towards parking facility and suggest the solutions to increase efficiency of parking facility. The scope of this research is focusing on the parking facilities provided at shopping complexes in Penang. A total of 300 questionnaires was distributed to three shopping malls which were Gurney Plaza, Gurney Paragon and Queensbay Mall. Out of 300 questionnaires distributed, only 276 questionnaires were returned back by the respondents. The collected data were transferred to SPSS software which the outcome has been in the form of table and bar chart. The result from the survey showed that the levels of satisfaction towards the facilities in the three shopping malls were between moderate to high. The level of agreement from each of the mall varies. Based on the data analysed, it can be observed that users at all the three shopping malls are most satisfied with the lighting provided at the parking area. The second most satisfied by users is panic button at shopping mall 2 and 3 and signage for shopping mall 1.